2017
DOI: 10.1089/jwh.2016.5807
|View full text |Cite
|
Sign up to set email alerts
|

Women's Contraceptive Preference-Use Mismatch

Abstract: While preference for effective contraception was common among this sample of women, we found substantial mismatch between preferred and usual methods, notably among women of lower socioeconomic status and women using less effective methods. Findings may have implications for patient-centered contraceptive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
(45 reference statements)
2
29
0
Order By: Relevance
“…We used Pearson's chi-squared test for bivariate analysis of sociodemographic variables and rating of contraceptive features as "very important." In multivariate logistic regression analysis of contraceptive preferences, we planned a priori to adjust for age, race/ethnicity, education, currently in school or working, ever pregnant, stable housing, history of an STI, and history of intimate partner violence (IPV) based on prior research findings [11,[15][16][17]. Variables associated with rating a feature "very important" in bivariate analysis with a pvalue ≤ 0.1 were also included in adjusted models.…”
Section: Methodsmentioning
confidence: 99%
“…We used Pearson's chi-squared test for bivariate analysis of sociodemographic variables and rating of contraceptive features as "very important." In multivariate logistic regression analysis of contraceptive preferences, we planned a priori to adjust for age, race/ethnicity, education, currently in school or working, ever pregnant, stable housing, history of an STI, and history of intimate partner violence (IPV) based on prior research findings [11,[15][16][17]. Variables associated with rating a feature "very important" in bivariate analysis with a pvalue ≤ 0.1 were also included in adjusted models.…”
Section: Methodsmentioning
confidence: 99%
“…This is unfortunate as studies have shown that many women, particularly low-income women, are interested in using a more effective form of contraception than they are currently using. 53 Notes: Adjusted for year, health insurance, age, race/ethnicity, income, education, and family type. * Indicates associations that were statistically significant (i.e., the 95% confidence interval does not include 1.00).…”
Section: Limitationsmentioning
confidence: 99%
“…A previous study done in Europe and South Africa showed that higher satisfaction rates among transdermal patch users were associated with higher adherence rates, compared to oral contraceptive (OC) users, who experienced both lower satisfaction rates and lower adherence rates [6,9]. The St. Louis Contraceptive CHOICE Project also showed that LARC (long acting reversible contraceptive) users exhibited both higher satisfaction (80% versus 54%) and continuation rates (86% vs. 55%) compared to OC users [6,7].…”
Section: Introductionmentioning
confidence: 96%
“…Perhaps satisfaction or dissatisfaction with a prior contraceptive method may influence doi: 10.7243/2054-9865-4-4 future choices (continuation or discontinuation of a method) and affect overall uptake of contraception. Apart from discontinuation, dissatisfaction with a method of contraception can further lead to non-use, improper use or switching to a less reliable method of contraception [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation